Opportunities and Challenges for Implementing Neurotrauma Prevention Program: A Practical Perspective for Developing Countries - Ghosh, Amrita; Pal, Ranabir; Moscote-Salazar, Luis Rafael; Padilla-Zambrano, Huber Said; Deora, Harsh; Agrawal, Amit (Indian Journal of Neurotrauma, 2019)
Neurotrauma is an underestimated and less understood public health issue in low- and middle-income countries for which we need system-based approach to prevention plans. This study was initiated to find rationale of effective plan with projectile vision of neurotrauma prevention. In search of innovative ideas of neurotrauma prevention evidence was explored from the published literature research on traumatic brain injury. Evidence-based global guidelines on recommended content and scheduling on prevention of neurotrauma literature searches data were also synthesized and summarized from research in developed countries. Our study noted that a considerable number of victims of neurotrauma with death and disabilities put mammoth costs to the already compromised health systems of the low- and middle-income countries. We need systems-based four-pronged approach incorporating neurotrauma registry, neurotrauma surveillance, translational research programs, and current approved process for development of clinical guidelines for prevention.
Keywords: neurotrauma; prevention; challenges